EKSEKUSI HAK TANGGUNGAN DI BANK SYARIAH PASCA UNDANG-UNDANG NOMOR 3 TAHUN 2006 - Suhaimi, Suhaimi (UIN Fatmawati Sukarno Bengkulu, 2017)
The implications of Law No. 3 of 2006 on religious courts, that the authority of the religious court expanded that includes Islamic economics were showcased in Article 49, that the logical consequence aspects of constitutional courts religion to be the only court with jurisdiction over issues that occur against Islamic economics , Writing in this thesis aims to know how the setting and execution of a security interest in the post of Islamic Banks law No. 3 of 2006. In terms of the types and nature, this research includes the study of normative law, because it is done from a juridical standpoint. The approach used in this research is descriptive analysis, the authors describe all the existing materials and then analyze the content analysis method. From the research found that setting the execution of Responsibility Rights in Islamic banks is through the religious court and use the settings general civil law and the execution of Responsibility Rights in Islamic banks initiated by filing a subpoena in a religious court so that the court religion did session aan maning form of reprimand against customer default to meet its obligations as an Islamic bank customers, and than if customers do not do it next Islamic banks apply for the execution of Responsibility Rights to the customer. Head of religious courts provide execution Responsibility Rights determination to further instruct the religious court bailiff accompanied by two witnesses to the execution of the seizure of the object. Then notified of the seizure to all agencies associated with the land and the buildings on it were confiscated